ENSO Teleconnection to Interannual Variability in Carbon Monoxide Over the North Atlantic European Region in Spring - Liu, Yi; Liu, Jane; Xie, Min; Fang, Keyan; Tarasick, David W.; Wang, Honglei; Meng, Lingyun; Cheng, Xugeng; Han, Han; Zhang, Xun (Frontiers in Environmental Science, 2022)
Carbon monoxide (CO) is a major pollutant in the atmosphere. It is also a precursor of ozone and an important sink of tropospheric OH, making it important to the oxidation of the troposphere. Here we report a strong positive teleconnection between the El Niño–Southern Oscillation (ENSO) in winter (November to February) to tropospheric CO over the North Atlantic European region (NAE) in the following spring (March to May). This ENSO teleconnection is evident in trajectory-mapped airborne CO data (In-service Aircraft for a Global Observing System, IAGOS) over 2002-2019. CO concentrations in El Niño years are 5-20 ppbv higher than those in La Niña years over the NAE troposphere. The regional mean difference from the surface to 300 hPa is 9.4 ppbv (7.6% of the mean). The correlation coefficient (r) between the ENSO index and detrended CO concentrations in the NAE is 0.67 at 400 hPa and 0.63 near the surface, both statistically significant at the 95% level. Such a teleconnection is also observed in independent surface observations, with r ranging from 0.57 to 0.74, all at 95% significance level. From analysis of fire emissions and atmospheric conditions, combined with tagged CO simulations using a chemical transport model, GEOS-Chem, we conclude that this teleconnection results from the combined effects of ENSO on both biomass burning and atmospheric transport. We find that in El Niño years, CO emissions from biomass burning are significantly enhanced in Northern Hemispheric South America, Southeast Asia, and North America due to warmer air temperatures and lowered precipitation. In addition, ENSO enhances CO transport from these regions to the NAE by enhancing upward and northeastward motions in the fire regions, accelerating westerlies over 20°N-40°N, and prompting ascents over the Atlantic and descents over Europe, while reducing CO outflow at the eastern boundary of Europe. The combined effect of ENSO on both CO emissions and CO transport leads to interannual variability in tropospheric CO over the NAE.